Current legal issues concerning awqaf in Malaysia - Syed Abdul Kader, Sharifah Zubaidah; Md. Dahlan, Nuarrual Hilal (IIUM Press, 2017)
Waqf is an important institution in Islam, aimed at achieving social welfare when a person the wāqif’, dedicates his property as a charitable endowment for the ongoing benefit of a certain class of persons or the public at large generation after generation